Pemanfaatan Agen Hayati Trichoderma Dan Bakteri Pada Pengomposan Ageratum conyzoides. L, Tithonia diversifolia (Hemsley) A. gray Dan Ampas Sagu - Fenny Salomina Jensanura Asyerem (Fakultas Pertanian Universitas Papua, 2012)
Fungi and bacteria can act as biological control agents and also as decomposers. This study aimed to select Trichoderma spp and bacteria celullotic that have high ability cellulotic on medium CMC and to assess the ability of the microorganism selected in composting Ageratum conyzoides L., Tithonia diversifolia (Hemsley) A. Gray and waste sagoo. The analysis showed that diameter of clear zone bacteria cellulotic larger than Trichoderma spp, using Trichoderma spp and cellulotic bacteria selected able to accelerate the composting process and affect the concentration of carbon, nitrogen content increased, the C/N ratio, pH and nutrient content of compost.